A social cure in the community: A mixed‐method exploration of the role of social identity in the experiences and well‐being of community volunteers. (2nd February 2021) - Bowe, Mhairi; Gray, Debra; Stevenson, Clifford; McNamara, Niamh; Wakefield, Juliet R. H.; Kellezi, Blerina; Wilson, Iain; Cleveland, Michelle; Mair, Elizabeth; Halder, Moon; Costa, Sebastiano
Abstract: Cohesive, resilient communities are vital to the well‐being of residents. Uncovering the determinants of successful community identities is therefore essential to progressing the community health agenda. Engaging in community participation through volunteering may be one pathway to building local community identity and enhancing residents' health and well‐being, but the group processes connecting them remain unexplored. We conducted two studies investigating these dynamics using the "Social Cure" perspective. First, we analysed 53 in‐depth interviews with volunteers, finding that community relationships shaped their experiences and that volunteering influenced their sense of community belonging, support, and well‐being. Second, a community survey ( N  = 619) revealed that volunteering predicts well‐being through the serial mediators of community identification and social support. Our article demonstrates the Social Cure processes involved in community‐based volunteering, their impact on community identity, support and well‐being, and their implications for community health, and the provision and sustainability of community voluntary action and interventions.